Fabrication of magnetic BaFe12O19/Ag3PO4 composites with an in situ photo-Fenton-like reaction for enhancing reactive oxygen species under visible light irradiation. Issue 10 (26th April 2019) - Xu, Yuanguo; Ge, Feiyue; Xie, Meng; Huang, Shuquan; Qian, Junchao; Wang, Hefei; He, Minqiang; Xu, Hui; Li, Huaming
Abstract : An in situ photo-Fenton-like and magnetic recycle system, BaFe12 O19 /Ag3 PO4 has been constructed. BaFe12 O19 can catalyze the conversion of H2 O2 to generate ROSs (˙O2 − and ˙OH radicals) on the surface of Ag3 PO4 . Abstract : This research was designed to synthesize a magnetic in situ Fenton-like photocatalyst using simple methods. The sheet materials of BaFe12 O19, with inherent magnetic properties, decorated with Ag3 PO4 and in situ catalytic conversion of H2 O2 generated on the surface of Ag3 PO4 could produce more reactive oxygen species (ROS) for degradation of organic pollutants via a photo-Fenton process. ESR, trapping experiments of different scavengers and H2 O2 detection proved that the ROS of oxidation of bisphenol A is mainly produced by the Fenton-like reaction. This work has effectively improved the degradation activity of Ag3 PO4 . Simultaneously, the BaFe12 O19 /Ag3 PO4 composite can be easily separated from the reaction system via applying an external magnetic field, and shows promising applications for the photo-oxidative degradation of environmental contaminants.